2014
DOI: 10.1111/fare.12061
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Poverty and the Transition to Adulthood

Abstract: The authors used the Panel Study of Income Dynamics 2007 Transition to Adulthood data in combination with the 2002 Child Development Supplement to examine social class bifurcation in young adulthood. Results indicate that poor youth possibly take on adult roles “too early” at the same time that high-income youth may be supported for a long period past their 18th birthday. Although not all evidence is consistent with this bifurcated story, childhood poverty does play a key role. Young adults from poor families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 18 publications
1
25
0
2
Order By: Relevance
“…We followed the literature (Kendig et al, ; Letkiewicz & Fox, ) to delete observations with missing values. In the data cleaning process of TAS, we deleted observations with missing values in financial independence and self‐efficacy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We followed the literature (Kendig et al, ; Letkiewicz & Fox, ) to delete observations with missing values. In the data cleaning process of TAS, we deleted observations with missing values in financial independence and self‐efficacy.…”
Section: Methodsmentioning
confidence: 99%
“…Lee and Mortimer () showed that a teenager's communication with parents regarding work helps foster economic self‐efficacy and then financial independence during the young adulthood. Kendig, Mattingly, and Bianchi () tested the influence of childhood poverty on the financial independence during young adulthood from the age 18 to 24 and found young adults from poor families achieve financial independence earlier. Rather than studying the effect of financial socialisation during the adolescence and poverty experience in earlier years, our study of young adults from the age 18 to 27 focuses on the relationship between the family income during adolescence and financial independence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research at the exosystem level has focused on the career development of children from poor social class. Although these children seem to present low academic aspirations and high risk for school dropout (Ferreira et al, 2007;Kendig et al, 2014;Oketch et al, 2012), academic achievement was found to buffer these effects (Schmitt-Wilson & Welsh, 2012). The identification of other protective factors can be useful to design interventions aimed at attenuating social differences in children's careers (Schultheiss, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Children from slum areas present lower academic aspirations than those from non-slum areas, being this difference also evident in parents' expectations for their offspring (Oketch et al, 2012). Children from poor families were also less likely to pursue college and more likely to become parents, start an independent life and help their families pay bills earlier in adulthood than children from richer areas (Kendig, Mattingly, & Bianchi, 2014). Mothers' and fathers' socioeconomic status are also negatively related to patterns of dropping out of school and positive associations with career expectations and engagement in career projects (Ferreira et al, 2007;Sobral et al, 2009).…”
Section: Exosystemmentioning
confidence: 98%